A grave robbery ebook - Raybourn, Deanna (Veronica Speedwell Mystery,, 2024)
Veronica and Stoker discover that not all fairy tales have happy endings, and some end in murder, in this latest historical mystery from New York Times bestselling and Edgar Award–nominated author Deanna Raybourn. Lord Rosemorran has purchased a wax figure of a beautiful reclining woman and asks Stoker to incorporate a clockwork mechanism to give the Rosemorran Collection its own Sleeping Beauty in the style of Madame Tussaud’s. But when Stoker goes to cut the mannequin open to insert the mechanism, he makes a gruesome discovery: this is no wax figure. The mannequin is the beautifully preserved body of a young woman who was once very much alive. But who would do such a dreadful thing, and why?  Sleuthing out the answer to this question sets Veronica and Stoker on their wildest adventure yet. From the underground laboratories of scientists experimenting with electricity to resurrect the dead in the vein of Frankenstein to the traveling show where Stoker once toured as an attraction, the gaslit atmosphere of London in October is the perfect setting for this investigation into the unknown. Through it all, the intrepid pair is always one step behind the latest villain—a man who has killed once and will stop at nothing to recover the body of the woman he loved. Will they unmask him in time to save his next victim? Or will they become the latest figures to be immortalized in his collection of horrors?